Analisis faktor yang berhubungan dengan resiliensi remaja dengan orang tua bercerai di Yogyakarta - Fajriyati Nur Azizah; Ngatoiatu Rohmani; Sujono Riyadi (Universitas Jenderal Achmad Yani Yogyakarta, 2022)
Background: Teenagers relationship with their parents is one way for teenagers to communicate their needs. The challenge that arises when the parents are no longer together/divorced. Parents who are divorced and already have children will have a physical and psychological impact on the child. Objective: The study aimed to analyzes the factors that related to mental resilience of adolescents with divorced parents included age, gender, education, length of parents divorce time, and social support. Metode: This is descriptive analytic research with crossectional approach. Respondents are teenagers aged 10-24 years old totaling 30 people. CD-RISC used to measure resilience and was analyzed using Spearman's analysis. Result: There is no correlation between age, gender, education, length of time when parents are in conflict/divorce, and support for adolescents with resilience with a significance value of age and resilience being 0.073, gender with resilience being 0.801, education with resilience being 0.501, age with resilience being 0.801, conflicted/divorced parents with resilience is 0.059, and support with resilience is 0.508. Conclution: This study suggests that attention should be paid to the resilience of adolescents. Mental support and social suppot need to be taken from family and community to reduce the negative behaviour and to increase resilience. . Keywords: Adolescense, Resilience, Divorce